The Etiology and Clinical Features of Non-CAH Gonadotropin-Independent Precocious Puberty: A Multicenter Study - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (ENDOCRINE SOC, 2016)
Aim: The causes of gonadotropin-independent precocious puberty are diverse, and often have overlapping clinical and biochemical features. With the exception of congenital adrenal hyperplasia (CAH), disorders that cause gonadotropin-independent precocious puberty (GIPP) are uncommon. The literature is devoid of any large-scale studies on the etiologic distribution of GIPP. The aim of this study was to determine the frequency of each etiology in a cohort of patients with GIPP (excluding those with CAH), and to evaluate the clinical and laboratory features of these patients. Materials and Methods: This multicenter, nationwide web-based study collected data on patients who presented with non-CAH GIPP in Turkey. Results: Data were collected for 129 patients (102 girls and 27 boys) from 29 centers. Based on the data collected, the estimated prevalence of non-CAH GIPP in the studied population was 14 in 1 000 000 children. Functional ovarian cyst was the most common etiology, accounting for 37% of all cases, followed by McCune-Albright syndrome (MAS) (26%). Among the patients with MAS, 11.7% had fibrous dysplasia, 32.3% had caf-au-lait spots, and 52.9% had both. Human chorionic gonadotrophin-secreting tumors included choriocarcinoma of the liver, hepatoblastoma, and germ cell tumors of the sellar-suprasellar region and mediastinum. Patients with adrenocortical tumors presented at an earlier age than those with other etiologies. Ovarian tumors included mature cystic teratoma, dysgerminoma, juvenile granulosa tumor, and steroid cell tumor. Despite overlapping features, it was possible to identify some unique clinical and laboratory features associated with each etiology. Conclusion: This largest cohort of patients with non-CAH GIPP to date yielded an estimation of the frequency of non-CAH GIPP in the general pediatric population and showed that girls were affected at a rate 4-fold greater than that of boys owing to functional ovarian cysts and MAS, which were the two most common etiologies. The data collected also provided some unique characteristics associated with each etiology.
Keywords: MCCUNE-ALBRIGHT-SYNDROME; JUVENILE HYPOTHYROIDISM; ADRENOCORTICAL TUMORS; EXPERIENCE; MUTATIONS